La ceramica greca figurata di Incoronata e della costa ionica dell'Italia meridionale nel VII secolo a.C. - Denti, Mario (Publications du Centre Jean Bérard, 2025)
This research deals with the study of figured pottery made by some Greek painters who, in the seventh century BC, crossed the Mediterranean to come to settle on the Ionian coast of southern Italy. Through a philological examination of the archaeological documentation and the iconographic and stylistic repertoire, the book traces a profile of the cultural identity of the potters who helped build this main historical phenomenon of the Mediterranean Iron Age. Thanks to the new data emerging from recent archaeological research – especially on the key site that illuminates today in a decisive way this scenario, Incoronata – it has been possible to frame such exceptional material and figurative manifestations within their own contexts of production and use: they were realized especially among those indigenous communities that, by welcoming these individuals and these goods, and participating in a shared ideological and cultural horizon, they have built a fundamental instrument of their historical-political hegemony. The book intends to follow the traces of these images, of these vessels, but above all of these people, trying – as far as possible – to understand their deepest historical significance.